The first step is to choose one option and rewrite it in the explicit form
I will choose the second option:
![y-3=(2)/(3)(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/fc399kmc6ope1yajrzuf3rc6723kgcx1mu.png)
![y=(2)/(3)(x-3)+3](https://img.qammunity.org/2023/formulas/mathematics/college/vdzzh18i1o7eln5vuw37poa63uasv8l26e.png)
![y=(2)/(3)x-2+3](https://img.qammunity.org/2023/formulas/mathematics/college/1oq1u354a3dbze5gsfan7oe1i2k0agwjq5.png)
![y=(2)/(3)x+1](https://img.qammunity.org/2023/formulas/mathematics/college/vowsdgkvtm380r0eybcvp7rbbyrdpj86on.png)
Now replace the x points in the equation to verify if it satisfies their respective value in y
For x=3
![y=(2)/(3)(3)+1=(6)/(3)+1=2+1=3](https://img.qammunity.org/2023/formulas/mathematics/college/y08lmszh0mb7chw8w9og5qcu9opqm55u9a.png)
For x=3 satisfy y=3
Now x=6
![y=(2)/(3)(6)+1=(12)/(3)+1=4+1=5](https://img.qammunity.org/2023/formulas/mathematics/college/zgfolmmowkugg8lcy32gha33g3wshliw82.png)
For x=6 satisfy y=5
So the answer is b.